Adenosine Vs Verapamil: Treating No-Reflow Phenomenon in Individuals with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention (PCI) - Zuhaib Zahoor Soomro; Muhammad Waqas; Muhammad Hassan; Imran Ellahi Soomro; Shahbaz Ali; Javed Khurshed Shaikh; Fawad Farooq, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: A condition that results from an imbalance between coronary blood supply and myocardial oxygen demand is called acute coronary syndrome (ACS). The no-reflow phenomenon is one of the most challenging complications for ACS which occurs during percutaneous coronary intervention (PCI). A few microvascular dysfunction mechanisms are included in the pathophysiology of the no-reflow phenomenon. These medicines include two names that are commonly used; adenosine and verapamil. Adenosine is a strong drug which is used to activate special A2 receptors that eventually help in opening up small blood vessels in the heart. On the other hand, verapamil is also used to relax the small blood vessels. Through this drug, the amount of calcium that enters into the muscle cells in the vessel walls is reduced. Objective: To compare the efficiency of adenosine with verapamil to treat no-reflow phenomenon in individuals with acute coronary syndrome undergoing percutaneous coronary intervention (PCI). Study design: An observational study Duration and place of study: This study was conducted in Peoples University of Medical and Health Sciences for Women Shaheed Benazirabad Nawabshah from August 2023 to August 2024 Methodology: This is an observational study which was performed in the Cardiology Department of the hospital. There were a total of 120 individuals who were a part of this study. They all were having an age of 18 years or older. All the participants of this study were having acute coronary syndrome (ACS). Along with this, they required percutaneous coronary intervention (PCI). All the patients were divided into 2 groups equally. Each group had 60 individuals. One group received intracoronary verapamil while the other group received adenosine.Variables such as IMR, TIMI, and FMD were expressed in terms of mean with standard deviations. To analyse the data, SPSS version 25 was used. Results: There were a total of 160 people included in this research. They all were having an age of 18 years or older. All the participants of this study were divided into 2 groups with each group having 60 individuals. One group received intracoronary verapamil while the other group received adenosine. The majority of the individuals were males in both the groups. The average age of the verapamil group was 60 years while it was 61 years for the adenosine group. Conclusion: In our study, both drugs, adenosine and verapamil, are effective but verapamil was found to be statistically significant in helping improve TIMI flow grades.